2020
DOI: 10.1007/s00127-020-01951-4
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of antidepressant use among refugee and Swedish-born youth after diagnosis of a common mental disorder: findings from the REMAIN study

Abstract: Purpose The objective of this study was to compare the initiation and type of antidepressant use between refugees and matched Swedish-born youth after a diagnosis of a common mental disorder (CMD) and assess sociodemographic and clinical factors associated with the initiation. Methods The study cohort included youth aged 16–25 years, with an incident diagnosis of CMD based on specialized health care registers in Sweden 2006–2016, without prior antidepressant use during 1 year. One Swedish-born person was mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 32 publications
3
9
0
Order By: Relevance
“…Comparing the ‘Low constant’ and ‘Low increasing’ trajectories between refugees and the Swedish-born reveals that, in general, proportions of refugee suicide attempters using antidepressants were somewhat lower than that among the Swedish-born. This is in line with previous research that reported lower psychiatric healthcare use [ 9 , 30 ] and treatment [ 29 ] in refugees than the host population. On the one hand, this may suggest that refugees have unmet needs for the treatment of their mental ill-health.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Comparing the ‘Low constant’ and ‘Low increasing’ trajectories between refugees and the Swedish-born reveals that, in general, proportions of refugee suicide attempters using antidepressants were somewhat lower than that among the Swedish-born. This is in line with previous research that reported lower psychiatric healthcare use [ 9 , 30 ] and treatment [ 29 ] in refugees than the host population. On the one hand, this may suggest that refugees have unmet needs for the treatment of their mental ill-health.…”
Section: Discussionsupporting
confidence: 93%
“…In a cross-sectional study in 2009, the prevalence of antidepressant use among refugees was considerably lower in refugees than in Swedish-born [ 28 ]. Much stronger differences between refugees and Swedish-born were found in a study focusing on young individuals with common mental disorders which reported considerably lower initiation of antidepressants in young refugees than their Swedish-born peers [ 29 ]. These contrasting findings regarding the degree of difference in antidepressant treatment in refugees, compared to host population, might be due to differences in study populations i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Such decision was motivated by several reasons, First, United Nations High Commissioner for Refugees (UNHCR) advocates to consider the family members and dependents of a refugee as 'refugee' [56]. Another important reason was to be consistent with other research for the sake of comparability [13]. Additionally, our sensitivity analysis confirmed the similarity of antidepressant trajectory groups across the sub-groups of the refugees, i.e., 'refugees defined by Geneva convention', 'in need of protection', 'humanitarian grounds' and 'family reunification to refugees'.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Although young refugees have an elevated risk of mental disorders, studies have shown that they tend to utilize psychiatric care and psychotropic drugs to a lower extent than their peers born in the host country [9][10][11][12][13]. This may be due to barriers in accessing healthcare in general and individual-level factors related to socio-cultural perceptions and attitudes, but also practical problems such as language difficulties when communicating with healthcare professionals [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation